New Challenges, New Tools for Defense Decisionmaking - Johnson, Stuart E. (RAND Corporation, 2003)
The collapse of the Soviet Union and the end of the Cold WarÑand then the terrorist attacks of September 11, 2001Ñtransformed the task of American foreign and defense policymaking. This book outlines the dimensions of that transformation and sketches new tools for dealing with the policy challengesÑfrom modeling and gaming, to planning based on capabilities rather than threats, to personnel planning and making use of "best practices" from the private sector.